The cholinergic pharmacology of tetrahydroaminoacridine in vivo and in vitro. - Hunter, A. J. (1989)
1. The effect of tetrahydroaminoacridine (THA) on cholinergically mediated behaviour in the rat and mouse has been investigated. In addition the actions of this compound on cholinesterase activity and on muscarinic and nicotinic receptors has also been examined. 2. Administration of THA (5-20 mg kg-1, i.p.) produced a dose-dependent increase in tremor, hypothermia and salivation in both rats and mice. A similar profile of activity was seen following physostigmine (0.1-0.6 mg kg-1) administration. 3. THA was approximately fifty fold less potent than physostigmine in inducing behavioural change but its effects persisted for over twice as long as those of physostigmine. For example THA-induced hypothermia was still present at 4 h in the mouse and 8 h in the rat. 4. In vitro THA was a potent non-competitive inhibitor of rat brain cholinesterase (IC50: 57 +/- 6 nM) and bovine erythrocyte acetylcholinesterase (IC50: 50 +/- 10 nM) but was a more potent inhibitor of horse serum butyrylcholinesterase (IC50: 7.2 +/- 1.4 nM). 5. Radioligand binding studies indicated that THA binds non-selectively but with moderate potency to both M1 (Ki: 600 nM) and M2 (Ki: 880 nM) muscarinic receptors. THA also interacted with the allosteric site present on cardiac M2 receptors. 6. It is concluded that THA is a reversible non-competitive inhibitor of cholinesterase with a long half life (compared with physostigmine). It also may antagonize muscarinic receptors at high doses. The long half life may account for its reported efficacy in the treatment of Alzheimer's disease.